Effect of flexural stiffness distribution of a ski on the ski-snow contact pressure in a carved turn - Yoneyama, T.; Kagawa, H.; Tatsuno, D.; Kitade, M.; Osada, K.; Shigehara, S. (Sports Engineering, 2021)
The design of the flexural stiffness distribution of a ski is one of the important factors in its development. On the other hand, the ski-snow contact pressure during a turn is thought to be an important factor in a skier`s feeling. However, the relationship between the flexural stiffness distribution and ski-snow contact pressure has not been made clear. The purpose of this study was to understand how flexural stiffness distribution affects the contacting pressure, applying load, and ski-snow contacting condition through measurement on these items. The measurement system consisted of a ski deflection sensor beam with bending sensors, pressure sensors installed near the ski edge, and four points of load cells connected between the binding plate and the ski. Measurements were performed on the different flexural stiffness distributions of Skis A and B on hard snow and soft snow surfaces. The peak of the flexural stiffness of Ski A was on the boot center, and Ski B was stiffer with a peak under the heel of the boot. An increase in the flexural stiffness under the heel of the boot for Ski B caused less deflection in the rear part of the ski, and the applied force from the binding plate shifted forward. By fitting the ski deflection on the snow groove, so the rear section of the ski after the pressure peak fitted on the sliding surface of the snow groove, the compression zone increased and the sliding zone was reduced in Ski B. The pressure peak in Ski A was under the boot center, whereas, for Ski B it was behind the boot center. These results show that changes in flexural stiffness distribution alter ski deflection and ski-snow contact pressure.